One of the guys: women as aggressors and torturers - McKelvey, Tara (Seal Press, 2007)
Foreword: Feminism's assumptions upended / Barbara Ehrenreich -- Introduction / Tara McKelvey -- Abu Ghraib : it's like an S&M club, only it's real / Eve Ensler -- Sexual coercion, prisons, and female responses / Angela Davis -- Why did Jennifer Scala bring cunt into the courtroom? / Ada Calhoun -- Split screens / Karen J. Greenberg -- The women of Abu Ghraib / Francine D'Amico -- The misogynist undercurrents of Abu Ghraib / Lucinda Marshall -- Shock and awe : Abu Ghraib, women military police, and racially gendered torture / Ilene Feinman -- Gender and sexual violence in the military / Jumana Musa -- Women soldiers and interrogational abuses in the war on terror / Steven H. Miles -- The "mean girls" of Abu Ghraib / Erin Solaro -- Guarding women : Abu Ghraib and military sexual culture / Elizabeth L. Hillman -- "Beautiful souls" : the role of women in war / Aziz Huq -- Photography/pornography/torture : the politics of seeing Abu Ghraib / Laura Frost -- Gender trouble at Abu Ghraib? / Timothy Kaufman-Osborn -- Is that the pose of a liberated woman? / Elizabeth Maddock Dillon -- Feminism as imperialism / Katharine Viner -- The "sex interrogators" of Guantanamo / Kristine A. Huskey -- Women in the interrogation room / Riva Khoshaba -- Women's role in mob violence : lynchings and Abu Ghraib / LaNitra Walker -- George W. Bush and the war on women / Barbara Finlay -- Lynndie England in love / Janis Karpinski -- The military made me do it : double standards and psychic injuries at Abu Ghraib / Lila Rajiva -- Afterword / Cynthia Enloe